Invertebrate models of lamin diseases - Rzepecki, Ryszard (Nucleus, 2018)
Lamins are evolutionarily conserved nuclear intermediate filament proteins. They provide structural support for the nucleus and help regulate many other nuclear activities. Mutations in human lamin genes, and especially in the LMNA gene, cause numerous diseases, termed laminopathies, including muscle, cardiac, metabolic, neuronal and early aging diseases. Most laminopathies arise from autosomal dominant missense mutations. Many of the mutant residues are conserved in the lamin genes of the nematode Caenorhabditis elegans and the fruit fly Drosophila melanogaster. Our current understanding of the mechanisms leading to these diseases is mostly based on patients cell lines and animal models including C. elegans and D. melanogaster. The simpler lamin system and the powerful genetic tools offered by these invertebrate organisms greatly contributed to such studies. Here we provide an overview of the studies of laminopathies in Drosophila and C. elegans models.